2015
DOI: 10.4103/1658-354x.154696
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between sugammadex and neostigmine in neurosurgical anesthesia in pediatric patients

Abstract: Background:Postoperative recurarization remains a risk following the use of the conventional neuromuscular blocking agents. In addition, none of the commonly used reversal agents, such as neostigmine or edrophonium are capable of reliably reversing profound blockade. The present comparative and randomized study investigated the use of sugammadex for reversing profound neuromuscular blockade (NMB) in pediatric neurosurgical patients undergone posterior fossa tumor excision.Patients and Methods:Forty pediatric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Matching with our outcome, Ghoneim et al, used sugammadex in a dose of 4 mg/kg at reappearance of T2 of TOF to reverse rocuronium‐induced NMB in paediatric patients undergoing neurosurgery. The recovery time was statistically shorter in the sugammadex group (1.4 ± 1.2 min) than those in neostigmine group (25.2 ± 6.5 min) without PORC or any major adverse events in any patient throughout the study period.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Matching with our outcome, Ghoneim et al, used sugammadex in a dose of 4 mg/kg at reappearance of T2 of TOF to reverse rocuronium‐induced NMB in paediatric patients undergoing neurosurgery. The recovery time was statistically shorter in the sugammadex group (1.4 ± 1.2 min) than those in neostigmine group (25.2 ± 6.5 min) without PORC or any major adverse events in any patient throughout the study period.…”
Section: Discussionmentioning
confidence: 64%
“…Multiple trials have reported safety and superiority of sugammadex over neostigmine for reversal of NMB in adults . However, few studies have concerned sugammadex use in paediatric patients …”
mentioning
confidence: 99%
“…In one study 26 reversal agents were administered at different times between the sugammadex group (PTC < 2–3) and the control group (PTC > 2–3), which we believe may have influenced the primary outcome. We believe that one trial 23 had a low risk of bias because all of the study criteria were assessed as low risk, whereas three trials 25, 26, 28, 30, 31 had high risks, and the risks of other studies 24, 27, 29, 32 were unclear. Assessments of risk of bias are summarized in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Six studies 2427, 29, 32 were unclear about their allocation concealment. Four studies 24, 25, 29, 31 did not report whether the patients and the assessors were blinded during outcome assessments. In the study conducted by El sayed 30 , the assessors were not blinded to the allocation of groups, which may have affected the results of the study; therefore, we evaluated the study as ‘high risk’.…”
Section: Resultsmentioning
confidence: 99%
“…Several other prospective studies have compared reversal of neuromuscular blockade using sugammadex with the acetylcholinesterase inhibitor, neostigmine (►Table 1). [27][28][29][30][31] These five prospective trials involving a total of 287 pediatric patients have demonstrated various clinical advantages of sugammadex over neostigmine including a more rapid return of the TOF ratio to ! 90% and a shorter time to tracheal extubation with sugammadex than with neostigmine.…”
Section: Sugammadex: Pediatric Applications Prospective Perioperativementioning
confidence: 99%